Security Dilemma Between USA and China: A Strategic Perception Approach - Kanellopoulos, Anastasios Nikolaos (HAPSc Policy Briefs Series, 2023)
This paper approaches the "Security Dilemma" as the cornerstone of Realist school of thought strategic Theory. According to that, states are regularly trapped into competition escalations, due to the lack of a clear “opponent” strategy and operational decisions’ understanding. This situation, leads to political distrust, occurring economical rivalries and military conflicts. Subsequently, 21st century China’s commercial and military power rising, creates fear for the states in the East Asia region and the global naval powers, a situation that promotes a new world competition between USA and China.